A prospective study on the incidence of contrast-associated acute kidney injury after recanalization of chronic total coronary occlusions with contemporary interventional techniques. (15th August 2021) - Werner, Gerald S.; Lorenz, Simon; Yaginuma, Kenji; Koch, Mathias; Tischer, Karlheinz; Werner, Juliane; Keuser, Thomas; Moehlis, Hiller; Riegel, Werner
Abstract: Background: Contrast-associated acute kidney injury (CA-AKI) is a potential risk associated with the percutaneous coronary interventions (PCI) for chronic total coronary occlusions (CTO). This study should evaluate the incidence of CA-AKI in an era of advanced strategies of recanalization techniques and identify modifiable determinants. Methods: We analysed 1924 consecutive CTO procedures in 1815 patients between 2012 and 2019. All patients were carefully monitored at least up to 48 h after a CTO procedure for changes in renal function. Results: The incidence of CA-AKI was 5.6%, but there was no relation to the technical approach such as frequency of the retrograde technique, intravascular ultrasound or radial access. Procedures with CA-AKI had longer fluoroscopy times (37.6 vs 46.1 min; p = 0.005). The major determinants of CA-AKI were age, presence of diabetes and reduced ejection fraction, as well as chronic kidney disease stage ≥2, serum haemoglobin, and fluoroscopy time. Contrast volume or contrast volume/GFR ratio were not independent determinants of CA-AKI. Periprocedural perforations were more frequent in CA-AKI patients (11.3 vs 2.3%; p < 0.001), and in-hospital mortality was higher (2.8 vs 0.4%; p < 0.001). Conclusions: CA-AKI was associated with the risk of in-hospital adverse events. Established patient-related risk factors for CA-AKI (age, diabetes, preexisting chronic kidney disease, low ejection fraction) were confirmed in this study. In addition, the length of the procedure, coronary perforations and low preprocedural serum haemoglobin were risk factors that might be preventable in patients at high risk for CA-AKI. Highlights: CA-AKI is a major procedural complication in patients undergoing complex PCI such as the recanalization of a CTO In a large cohort of 1924 procedures the incidence of CA-AKI was 5.6%, in patients with CKD it increased to about 20%. Patient-related risk factors were higher age, diabetes, LVEF<40%, pre-existing CKD, as well as preprocedural anaemia. Procedural risk factors were longer procedures, and the risk of perforation, but not the contrast medium volume. It should be tested in further studies whether correcting anaemia in patients at highest risk could reduce CA-AKI.